Literature Review: The Effect of Wages on Performance of Shopping Center Employees in Surabaya - Moh. Maruf; Putra, Riyan Sisiawan; Nurcahya Setiani Rahayu; Heni Agustina; Hidayatul Khusnah (Universitas Nahdlatul Ulama Sidoarjo, 2023)
Human resources hold an important position in a company, because the human factor is the most important driver in every activity within the company, because employees carry out company activities from planning, implementing, to controlling every activity and activities of the Company. This research aims to determine the effect of wages on the performance of shopping center employees in Surabaya. The research carried out was a Literature Review Using the Systematic Literature Review Method. Final findings include variables that have been researched extensively, namely the influence of wages on performance among shopping center employees in Surabaya. The research results show that the Wage Variable has a significant influence on the dependent variable, namely Employee Performance. It is hoped that the findings of this research can help Shopping Centers in Surabaya to pay more attention to and improve employees who show good work results at the Company, so that they can become role models for other employees, that providing decent wages from leaders can improve employee performance.